Nutritional Intervention through Education and Supplementary Food Provision to Fostered Families with a Family Doctor Approach in Uteunkot Village, Muara Dua District, Lhokseumawe - Noviana Zara; Mardiati (HM Publisher, 2021)
Indonesia as a developing country still has some gaps and shortcomings in health problems, one of which is nutritional problems. Based on the 2018 Global Nutrition Report, Indonesia is included in 17 countries that have complex nutritional problems, like stunting, wasting and overweight. Aceh Province in 2018 reported that there were 16.8% undernourished children under five and 6.7% malnourished children, while 2.9% were overweight. One of the things that can be done in overcoming these problems is through nutritional intervention to the community. Therefore, this research was conducted as a form of nutrition intervention through education and supplementary feeding (PMT) to the assisted families with a family medicine approach in Uteunkot Village, Muara Dua District, Lhokseumawe. The measuring instrument used is a balanced nutrition questionnaire which has been tested for validity and reliability to assess the level of knowledge of respondents about balanced nutrition. In addition, education on balanced nutrition and supplementary feeding is also carried out. The sampling technique used is total sampling with a total of 79 respondents. The results of the distribution of the level of knowledge of respondents on balanced nutrition before being given education were the most in the poor category with a total of 41 people (51.9%), after an intervention in the form of education obtained the distribution of the level of knowledge of respondents about balanced nutrition in the good category with a total of 69 people (87.3%). In addition, it was also found that almost all respondents consumed the given Supplementary Food